Decision Making System for Acceptance of Teaching Staff at Pondok Anugerah Special School with Simple Additive Weighting (SAW) Method - Darmayanti, Putri; Ginting, Subhan Hafiz Nanda; Rambe, Aripin (Journal of Technology and Computer, 2024)
Special School (SLB) is a means of gaining knowledge for children with special needs. The quality of the school is inseparable from the quality of the teachers who provide teaching and education. Selecting prospective teachers who will teach and educate in schools is one way to improve school quality. Teacher recruitment is carried out to find teaching staff that suits the needs of the school based on the criteria determined by the school. Acceptance of teaching staff at this school is only by interview tests without going through the selection stage to see the talents and abilities of prospective teaching staff, after which the school negotiates by asking the teacher's approval for the acceptance of prospective teachers, so that the quality of prospective teachers to teach students with special needs is not so prominent, which results in ineffective criteria for the desired teacher to care for or guide students. A system that can help produce accurate assessment results by implementing a Decision Support System (SPK) is needed. One of the decision support system methods is the Simple Additive Weighting (SAW) method. The SAW method is a method that uses several assessment criteria that are important factors in the selection of teacher acceptance. The assessment criteria include education, experience, age, and the results of oral tests and interviews. From the results of these criteria will produce the assessment weight of each prospective teaching staff, then calculations will be carried out to find the ranking results based on the highest to lowest priorities. This research produces an information system to assist leaders in making the right decisions in the process of recruiting teaching staff at SLB Pondok Anugerah by applying the SAW method.